Identification of a rapidly‐spreading triple mutant for high‐level metabolic insecticide resistance in Anopheles gambiae provides a real‐time molecular diagnostic for antimalarial intervention deployment. Issue 16 (12th July 2022) - Njoroge, Harun; van't Hof, Arjen; Oruni, Ambrose; Pipini, Dimitra; Nagi, Sanjay C.; Lynd, Amy; Lucas, Eric R.; Tomlinson, Sean; Grau‐Bove, Xavi; McDermott, Daniel; Wat'senga, Francis T.; Manzambi, Emile Z.; et al.
Abstract: Studies of insecticide resistance provide insights into the capacity of populations to show rapid evolutionary responses to contemporary selection. Malaria control remains heavily dependent on pyrethroid insecticides, primarily in long lasting insecticidal nets (LLINs). Resistance in the major malaria vectors has increased in concert with the expansion of LLIN distributions. Identifying genetic mechanisms underlying high‐level resistance is crucial for the development and deployment of resistance‐breaking tools. Using the Anopheles gambiae 1000 genomes (Ag1000g) data we identified a very recent selective sweep in mosquitoes from Uganda which localized to a cluster of cytochrome P450 genes. Further interrogation revealed a haplotype involving a trio of mutations, a nonsynonymous point mutation in Cyp6p4 (I236M), an upstream insertion of a partial Zanzibar‐like transposable element (TE) and a duplication of the Cyp6aa1 gene. The mutations appear to have originated recently in An. gambiae from the Kenya‐Uganda border, with stepwise replacement of the double‐mutant (Zanzibar‐like TE and Cyp6p4‐236 M ) with the triple‐mutant haplotype (including Cyp6aa1 duplication), which has spread into the Democratic Republic of Congo and Tanzania. The triple‐mutant haplotype is strongly associated with increased expression of genes able to metabolize pyrethroids and is strongly predictive of resistance to pyrethroids most notably deltamethrin. Importantly, there was increased mortality in mosquitoes carrying the triple‐mutation when exposed to nets cotreated with the synergist piperonyl butoxide (PBO). Frequencies of the triple‐mutant haplotype remain spatially variable within countries, suggesting an effective marker system to guide deployment decisions for limited supplies of PBO‐pyrethroid cotreated LLINs across African countries.